Overview of Patient Family Satisfaction About Emergency Room Services at RSUD dr. Soedono Madiun - Guritno, Punjung; Suprajitno, Suprajitno; Mujito, Mujito (Poltekkes Kemenkes Malang, Campus III Blitar, 2025)
Patient family satisfaction is a perception of the patient's family of the services provided to the patient with what the patient's family expects, so that the services provided to patients can affect patient family satisfaction. Patient family satisfaction is affected by service quality which consists of tangible, reliability, responsiveness, assurance, and empathy. This research aims to determine the overview of patient family satisfaction about the emergency room services at RSUD dr. Soedono Madiun. This research uses descriptive design and quantitative research type with 40 respondents taken by purposive sampling. Data analysis in this study is univariate. The results of this research indicate the patient's family satisfaction about the service at the emergency room RSUD dr. Soedono Madiun is mostly in the category of very satisfied satisfaction of 75%. Based on the 5 dimensions of service quality, the highest score is obtained in the assurance dimension and the lowest score is located in the tangible dimension. It can be said that the services in the emergency room provided are very good. Therefore, it is hoped that the services provided will maintain the quality of service, and even be improved for the better.